2017
DOI: 10.1371/journal.pone.0176626
|View full text |Cite
|
Sign up to set email alerts
|

Neural substrate of posterior left atrium: A novel modulation for inducibility and remodeling of atrial fibrillation in canine

Abstract: BackgroundThe neural mechanism of posterior left atrium (PLA) for genesis of atrial fibrillation has not been completely elucidated. We sought to assess the contribution of PLA denervation on atrial fibrillation (AF) inducibility and atrial remodeling.Methods and resultsAfter left thoracotomy in anesthetized dogs (n = 32), electrode catheters were attached to the PLA, left atrial roof, left pulmonary vein and left atrial appendage. Experiment 1 (n = 16): Vagal stimulation (VS group, n = 8) led to more pronounc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The density of nerve fibers in PV-LA junction is significantly higher than PV distal parts, and the sympathetic innervation appears to be superior. The regional differences in the conduction velocity and ERP of PLA and PV-LA as a result of anatomical properties [31][32][33] Notably, our study 38 also confirmed that intervention of PV ostium (including: RSPV anterior wall and LSPV apex, etc.) with radiofrequency ablation can produce significant vagal reactions manifested by sinus arrest and atrioventricular conduction delay; modification of this region can significantly decrease the postoperative recurrence rate (Figure 4).…”
Section: Innervation Regions Of Cans and Afsupporting
confidence: 75%
See 4 more Smart Citations
“…The density of nerve fibers in PV-LA junction is significantly higher than PV distal parts, and the sympathetic innervation appears to be superior. The regional differences in the conduction velocity and ERP of PLA and PV-LA as a result of anatomical properties [31][32][33] Notably, our study 38 also confirmed that intervention of PV ostium (including: RSPV anterior wall and LSPV apex, etc.) with radiofrequency ablation can produce significant vagal reactions manifested by sinus arrest and atrioventricular conduction delay; modification of this region can significantly decrease the postoperative recurrence rate (Figure 4).…”
Section: Innervation Regions Of Cans and Afsupporting
confidence: 75%
“…CANS is a highly integrated network, where the highly activated GP can release neurotransmitters by a proximal‐to‐distal gradient. The activation of axons from GP will then reversely activate the distant GP, thus leading to neurotransmitter release and inducing AF, which was explained by Sunny Po et al with the “octopus hypothesis.” Recent studies indicate that multiple intra‐atrial regions are innervated by the nerve fibers from GP, called atrial innervation region (IR) . However, the innervation function of IR is spatially heterogeneous, that is, the density of nerve fibers, M receptors and I K,Ach channel in the PLA and the junction of PV ostium and left atrium (PV‐LA) is greater than that in other left atrial regions; Tan et al also demonstrated that autonomic nerve density was highest in the LA within 5 mm of the PV‐LA junction by immunohistochemical staining on segments from normal human hearts .…”
Section: The Relationship Between Regulated Network Of Cans and Afmentioning
confidence: 99%
See 3 more Smart Citations